2013
DOI: 10.1186/1741-7015-11-209
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Assessment and Repair Longitudinal Study (PEARLS): a matched-pair cluster randomized trial

Abstract: BackgroundPerineal trauma during childbirth affects millions of women worldwide every year. The aim of the Perineal Assessment and Repair Longitudinal Study (PEARLS) was to improve maternal clinical outcomes following childbirth through an enhanced cascaded multiprofessional training program to support implementation of evidence-based perineal management.MethodsThis was a pragmatic matched-pair cluster randomized controlled trial (RCT) that enrolled women (n = 3681) sustaining a second-degree perineal tear in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 17 publications
0
37
1
7
Order By: Relevance
“…Therefore, the results showed that the educational intervention significantly improved the knowledge of professionals about the best perineal repair practices based on evidence, concluding that the permanent and standardized education is essential for the maintenance of improved care (13) . However, in the current study the results identified in the medical records showed that perineal lacerations and episiotomy rates increased by around four percentage points after the proposed intervention, but without a statistically significant difference.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the results showed that the educational intervention significantly improved the knowledge of professionals about the best perineal repair practices based on evidence, concluding that the permanent and standardized education is essential for the maintenance of improved care (13) . However, in the current study the results identified in the medical records showed that perineal lacerations and episiotomy rates increased by around four percentage points after the proposed intervention, but without a statistically significant difference.…”
Section: Discussionmentioning
confidence: 93%
“…This is despite the recognition that standards around perineal repair need to be improved nationally and internationally NICE, 2008;Kyei et al, 2012;Ismail et al, 2013). Variation in practice noted in this study appeared to be due to subjective, rule of thumb decisions made by clinicians.…”
Section: Discussionmentioning
confidence: 59%
“…The finding that women felt anxious about future functioning, healing or defecating was reflected by Way (2012) when women strived 'to be normal' (Way, 2012 p e712). Most recently, Bick (2014) identified that women who participated in the 'PEARLS' study (Ismail et al, 2013) felt the most important concern for them was around healing and future functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As clinicians, we often assume we know what the primary study outcome should be -however, health service users are really the experts in knowing which outcomes have the highest priority, highlighting that when planning research we need to consider our audience. In our recent perineal repair trial (7) , as clinicians we assumed pain would be the most important outcome for women who had a second degree tear or an episiotomy. When we asked the women who had sustained these perineal outcomes what their priorities were, they were most concerned about perineal wound infection.…”
Section: Editorialmentioning
confidence: 99%